SELF-SIMILARITY IN PITCH ORGANIZATION - Adrian BORZA (Studia Universitatis Babeş-Bolyai. Musica)
In this study we intend to discuss the self-similarity concept, which can be thought of as an organizing principle of the pitch of the sound. We will put emphasis on the self-similarity aspect of pitch organization in different series created by Anton Webern, and in several modes conceived by Olivier Massiaen, and Wilhelm Georg Berger. Also, we will investigate the author’s self-similar, non-octave-based, and full-chromatic mode of twenty-three notes, which led to the author’s compositions, such as Chaconne for guitar solo (1999), Fractus III for percussion and computer (2001), and Point. Line. Spot for string orchestra (2003).